Computer Science
Simplify the following expression and convert it into its canonical POS form:
(X.Y + Z)(Y + Z'.X)
Answer
Simplifying the expression:
(X.Y + Z)(Y + Z'.X)
= (X + Z).(Y + Z).(Y + Z').(X + Y)
= (XY + YZ + XZ + Z).(Y + Z').(X + Y)
= [XY + YZ + Z(X + 1)].(Y + Z').(X + Y)
= (XY + YZ + Z).(Y + Z').(X + Y)
= (XY + YZ + YZ + XYZ' + YZZ' + ZZ').(X + Y)
= [XY(1 + Z') + YZ + 0 + 0].(X + Y)*
= (XY + YZ).(X + Y)
= XY + XYZ + XY + YZ
= XY(1 + 1 + Z) + YZ
= XY + YZ
Converting to canonical POS form:
XY + YZ
= Y(X + Z)
= (Y + XX' + ZZ').(X + YY' + Z)
= (X + Y + Z).(X + Y + Z').(X' + Y + Z).(X' + Y + Z').(X + Y + Z).(X + Y' + Z)
= (X + Y + Z).(X + Y + Z').(X' + Y + Z).(X' + Y + Z').(X + Y' + Z)
Related Questions
Given F = A + (B + C).(D' + E)
Find F' and show the relevant working in steps.For the given truth table A, B and C are the inputs and X is the output.
A B C X 0 0 0 1 0 0 1 0 0 1 0 0 0 1 1 1 1 0 0 1 1 0 1 0 1 1 0 1 1 1 1 0 Write:
(i) Canonical Sum of Product expression (SOP).
(ii) Canonical Product of Sum expression (POS).State the distributive law. Verify it using the truth table.
Minimise the following expression. At each step clearly mention the law used.
Y.(A+B').(B+CD)'